ANALYSIS OF YOU C 1000 BEVERAGE MARKETING STRATEGY AT PT.ASIA SEJAHTERA PERDANA PHARMACEUTICAL: ANALISIS STRATEGI PEMASARAN MINUMAN YOU C 1000 PADA PT.ASIA SEJAHTERA PERDANA PHARMACEUTICAL - Suhandi Suhandi; Icin Quraysin (Yayasan Education and Social Center, 2021)
In an effort to maintain the sales performance of Youc 1000 drinks, there are many things that must be observed, among others, the more aggressiveness of several other beverage brands in marketing activities. The purpose of this study is to conduct research on the You C. regarding the acquisition process of new consumers, considering that there are many vitamin beverage industries on the market. Develop a marketing strategy that is deemed appropriate to carry out the acquisition of potential customers of You C 1000, through a large-scale promotional program that is right on target. Develop a marketing strategy that is deemed appropriate to reward loyal customers of You C 1000. The marketing strategy of You C 1000 health drink at PT Asia Sejahtera Perdana Pharmaceutical in the SWOT matrix analysis (figure 4.1) shows that the strategy is in an aggressive strategic position or is in the quadrant I or the growth quadrant where the company has the strength to face competition and has good opportunities. Strategic analysis illustrates that PT Asia Sejahtera Perdana Pharmaceutical has excellent strength. The weakness obtained from the analysis shows a weakness that is not difficult to repair or improve by PT Asia Sejahtera Perdana Pharmaceutical. Besides that, health drinks are also growing along with the increasing welfare and level of public awareness of health and stamina. One of the threat factors is the emergence of competitors with the same brand.